Exploration of the copper-sulfur deposit, Khayyam and Stumble-On properties, Prince of Wales Island, Alaska - Fosse, Earl L. ([Washington, D.C.] : U.S. Dept. of the Interior, Bureau of Mines, 1946)
"September 1946." Mode of access: Internet.